The synergistic immunotherapeutic impact of engineered CAR-T cells with PD-1 blockade in lymphomas and solid tumors: a systematic review - Satapathy, Bibhu Prasad; Sheoran, Pooja; Yadav, Rohit; Chettri, Dewan; Sonowal, Dhruba; Dash, Chinmayee Priyadarsini; Dhaka, Prachi; Uttam, Vivek; Yadav, Ritu; Jain, Manju; Jain, Aklank (Frontiers in Immunology, 2024)
Currently, therapies such as chimeric antigen receptor-T Cell (CAR-T) and immune checkpoint inhibitors like programmed cell death protein-1 (PD-1) blockers are showing promising results for numerous cancer patients. However, significant advancements are required before CAR-T therapies become readily available as off-the-shelf treatments, particularly for solid tumors and lymphomas. In this review, we have systematically analyzed the combination therapy involving engineered CAR-T cells and anti PD-1 agents. This approach aims at overcoming the limitations of current treatments and offers potential advantages such as enhanced tumor inhibition, alleviated T-cell exhaustion, heightened Tcell activation, and minimized toxicity. The integration of CAR-T therapy, which targets tumorassociated antigens, with PD-1 blockade augments T-cell function and mitigates immune suppression within the tumor microenvironment. To assess the impact of combination therapy on various tumors and lymphomas, we categorized them based on six major tumorassociated antigens: mesothelin, disialoganglioside GD-2, CD-19, CD-22, CD-133, and CD-30, which are present in different tumor types. We evaluated the efficacy, complete and partial responses, and progression-free survival in both pre-clinical and clinical models. Additionally, we discussed potential implications, including the feasibility of combination immunotherapies, emphasizing the importance of ongoing research to optimize treatment strategies and improve outcomes for cancer patients. Overall, we believe combining CAR-T therapy with PD-1 blockade holds promise for the next generation of cancer immunotherapy.